Access to the parapharyngeal space: An anatomical study comparing the endoscopic and open approaches. (17th May 2013) - Van Rompaey, Jason; Suruliraj, Anand; Carrau, Ricardo; Panizza, Benedict; Solares, C. Arturo
<x xml:space="preserve">Abstract</x> Objectives/Hypothesis A subtemporal preauricular approach to the infratemporal fossa and parapharyngeal space has been the traditional path to tumors of this region. The morbidity associated with this procedure has lead to the pursuit of less invasive techniques. Endoscopic access using a minimally invasive transmaxillary/transpterygoid approach potentially may obviate the drawbacks associated with open surgery. The anatomy of the parapharyngeal space is complex and critical; therefore, a comparison of the anatomy exposed by these different approaches could aid in the decision making toward a minimally invasive surgical corridor. Study Design Technical Note. Methods The parapharyngeal space was accessed endonasally by removal of the medial and posterior walls of the maxillary sinus. To allow better visualization and increased triangulation of a bimanual dissection technique, a sublabial canine fossa antrostomy was created. The medial and lateral pterygoid plates were removed. Further lateral dissection exposed the relevant anatomy of the parapharyngeal space. A subtemporal preauricular infratemporal approach was also completed. Results The endoscopic approach provided sufficient access to the superior portion of the parapharyngeal space. The open approach also provided adequate access; however, it required a larger surgical window, causing greater injury. A significant advantage of the subtemporal approach is the improved access to the petrous portion of the internal carotid artery. Conversely, the endonasal approach provided improved access to the anterior and medial portions of the superior parapharyngeal space. Conclusion Endoscopic endonasal access utilizing a transmaxillary/transpterygoid approach provides a sufficient surgical window for tumor extirpation. Utilization of this approach obviates some of the morbidity associated with an open procedure. Level of Evidence 5. Laryngoscope, 123:2378–2382, 2013